Gambaran Interleukin 6 dan Hepidin pada Penyakit Kronis yang Dapat Menyebabkan Anemia - Natasya G. Rorimpandey; Glady I. Rambert; Mayer F. Wowor (Universitas Sam Ratulangi, 2023)
Abstract: Anemia of chronic diseases is the second most common anemia after iron deficiency anemia. Hepcidin is a key factor that regulates iron metabolism, meanwhile interleukin 6 plays an important role in stimulating hepcidin mRNA. Chronic inflammation can stimulate macrophages to produce IL-6 and induce hepcidin, which will inhibit iron absorption in small intestine and also reduce iron release from macrophages resulting in anemia. This study aimed obtain the description of interleukin 6 and hepcidin in chronic diseases causing anemia inter alia tuberculosis, human immunodeficiency virus (HIV), rheumatoid arthritis (RA), inflammatory bowel disease (IBD), and systemic lupus erythematosus (SLE). This was a literature review using three databases namely PubMed, Google Scholar and Elsevier. The results obtained 15 literatures to be reviewed, consisting of three articles about tuberculosis, four articles about HIV, three articles about RA, three articles about IBD, dan two articles about SLE. Most literatures showed increased IL-6 and hepcidin levels, therefore, both could be used as diagnostic markers for anemia. Minimum and maximum levels that caused anemia in chronic diseases for IL-6 was 1.17-98.00 pg/ml and for hepcidin 0.5-228.1 ng/ml. In conclusion, in chronic diseases causing anemia, there are increases of IL-6 and hepcidin, therefore, they could be used as diagnostic markers for anemia. Keywords: interleukin 6; hepcidin; anemia of chronic diseases Abstrak: Anemia pada penyakit kronik merupakan anemia kedua terbanyak setelah anemia defisiensi besi. Hepsidin merupakan faktor kunci yang mengatur metabolisme zat besi sedangkan interleukin 6 berperan penting dalam merangsang mRNA hepsidin. Inflamasi kronis dapat merangsang makrofag untuk memroduksi IL-6 dan menginduksi hepsidin, menghambat penyerapan besi di usus halus dan juga menurunkan pelepasan besi dari makrofag sehingga terjadi anemia. Penelitian ini bertujuan untuk mengetahui gambaran interleukin 6 dan hepidin pada penyakit kronis yang dapat menyebabkan anemia, antara lain tuberkulosis, infeksi human immunodeficiency virus (HIV), rheumatoid arthritis (RA), inflammatory bowel disease (IBD) dan systemic lupus erythematosus (SLE). Jenis penelitian ini ialah suatu literature review dengan pencarian data menggunakan tiga sumber database yaitu PubMed, Google Scholar dan Elsevier. Hasil penelitian mendapatkan 15 literatur yang dilakukan review. Terdapat tiga artikel tentang tuberkulosis, empat artikel infeksi HIV, tiga artikel RA, tiga artikel IBD, dan dua artikel SLE. Sebagian besar literatur memperlihatkan peningkatan kadar IL-6 dan hepsidin sehingga keduanya dapat dijadikan penanda diagnostik anemia pada penyakit kronis. Nilai minimum dan maksimum IL-6 pada beberapa penyakit kronis yang dapat menyebabkan anemia ialah 1,17-98,00 pg/ml dan hepsidin 0,5-228,1 ng/ml. Simpulan penelitian ini ialah pada penyakit kronis yang dapat menyebabkan anemia terdapat peningkatan kadar IL-6 dan hepsidin sehingga keduanya dapat dijadikan penanda diagnostik anemia. Kata kunci: interleukin 6; hepsidin; anemia penyakit kronis